Innovative Online Formative Histology Assessment - Fauzia Nausheen; Tracey Weiler; David Graham; Dietrich E. Lorke (Association of American Medical Colleges, 2016)
Abstract Introduction We present a pair of approximately 50-minute, formative self-assessment, e-learning modules (histology quizzes) that evaluate student knowledge of basic histology and systems histology of the gastrointestinal (GI) tract. The modules integrate microscopic anatomy with cellular functions. Methods During the anatomy course, students are given four 50-minute lectures on histology with associated readings from the assigned textbook. During the GI course, students are given one 50-minute lecture accompanied by a reading assignment from the same textbook. The lecture learning objectives are consistent with the objectives of the Quizmaker modules. Subsequently, the relevant histology quiz is made available to the students. Although the assessments are formative, students are required to complete them with a passing grade of 80% in order to pass the course. Students are given unlimited attempts to achieve the passing grade. Results To date, a total of 320 students have completed the quizzes. The average of the Likert responses of the first-year medical students to the statement "The Histology and Radiology Quizmaker programs helped me to clarify concepts and identify areas of deficiency" was 4.3. Narrative comments were uniformly positive: students liked the program and greatly benefitted from it, suggested that the program be offered again and thanked the faculty for preparing it. Additional comments stated that the quizzes helped students recognize histological structures and study general histological concepts while integrating histology with other preclinical subjects. Discussion The Histology Quizmaker quizzes are very useful tools for formative self-assessment with immediate feedback, which are highly appreciated by the students. We plan to add similar histology tools in other second-year organ systems courses and in the third-year clinical clerkships to integrate the basic sciences with the clinical sciences.